Role of Selected Spectral Attributes in the Perception of Synthetic Vowels - Savela, Janne (Turku Centre for Computer Science, 2009)
This thesis is an experimental study regarding the identification and discrimination of vowels, studied using synthetic stimuli. The acoustic attributes of synthetic stimuli vary, which raises the question of how different spectral attributes are linked to the behaviour of the subjects. The spectral attributes used are formants and spectral moments (centre of gravity, standard deviation, skewness and kurtosis). Two types of experiments are used, related to the identification and discrimination of the stimuli, respectively. The discrimination is studied by using both the attentive procedures that require a response from the subject, and the preattentive procedures that require no response. Together, the studies offer information about the identification and discrimination of synthetic vowels in 15 different languages. Furthermore, this thesis discusses the role of various spectral attributes in the speech perception processes. The thesis is divided into three studies. The first is based only on attentive methods, whereas the other two concentrate on the relationship between identification and discrimination experiments. The neurophysiological methods (EEG recordings) reveal the role of attention in processing, and are used in discrimination experiments, while the results reveal differences in perceptual processes based on the language, attention and experimental procedure.